Non-selective, calcium-permeable channels in the apical membrane of rabbit renal tubules and in the basolateral membrane of human renal tubules : an exploratory patch clamp study - Saunders, James (MRC/UCT RU for Exercise and Sport Medicine, 2016)
Includes bibliography.